Age-Related Decline of Gastric Secretion: Facts and Controversies - Francisco Vara-Luiz; Ivo Mendes; Carolina Palma; Paulo Mascarenhas; Gonçalo Nunes; Marta Patita; Jorge Fonseca (Biomedicines)
Aging is associated with structural and functional changes in the gastrointestinal tract; however, its impact on gastric secretion remains unclear. This scoping review examines whether gastric secretion declines with age and explores its clinical implications. Following the PRISMA guidelines, PubMed, Web of Science, Embase, and Google Scholar were systematically searched from inception to December 2024. Fifteen studies (both animal and human) met the inclusion criteria: they were written in English, directly relevant to aging and gastric secretion, and had a clearly stated methodology. Evidence strength was assessed using the GRADE framework, revealing predominantly low to moderate certainty due to small sample sizes and observational study designs. Animal studies have demonstrated reduced acid secretion in older rats, which is attributed to mucosal atrophy and diminished responsiveness to gastrin. Recent human studies suggest that aging does not directly reduce acid output, as reduced acid secretion may result from a higher prevalence of atrophic gastritis, Helicobacter pylori infection, and the widespread use of proton pump inhibitors. Antisecretory therapy may lack benefits in older adult patients with hypochlorhydria/achlorhydria and increase the risk of adverse effects. Pepsin output declines with aging due to reduced chief cell function, although its clinical impact on digestion is unclear. Since intrinsic factor secretion far exceeds the amount necessary for its physiological function, even low amounts seem to be sufficient to prevent cobalamin deficiency. Age-related decline in gastric secretion is mostly attributed to age-associated disorders; however, impairment of secretory function in older people is frequent. Future research should prioritise longitudinal studies, larger cohorts, and histology-stratified analysis.